2014
DOI: 10.1111/camh.12065
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Issues: Review of four patient reported outcome measures: SDQ, RCADS, C/ORS and GBO – their strengths and limitations for clinical use and service evaluation

Abstract: Background There is an international drive for routine use of Patient Reported Outcome Measures (PROMs) across all health services including in relation to Child and Adolescent Mental Health Services (CAMHS). A number of reviews have summarized the validity and reliability of well‐being and mental health measures for children but there are fewer attempts to consider utility for routine use. Method This review considers four child self‐report measures: the Strengths and Difficulties Questionnaire (SDQ), the Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…All but three studies used standardized rating scales such as CBCL or SDQ and were rated as strong, as these measures are reliable and valid. 28,29 Two studies used case notes review and were rated a strong because this method is also reliable and valid. 30 Regarding the issue of participant withdrawals, studies were categorized as strong if there appeared to be no dropouts.…”
Section: Study Qualitymentioning
confidence: 99%
“…All but three studies used standardized rating scales such as CBCL or SDQ and were rated as strong, as these measures are reliable and valid. 28,29 Two studies used case notes review and were rated a strong because this method is also reliable and valid. 30 Regarding the issue of participant withdrawals, studies were categorized as strong if there appeared to be no dropouts.…”
Section: Study Qualitymentioning
confidence: 99%
“…It is also notable that a recent review was conducted by Wolpert and colleagues (2014) to compare to clinical utility between the following outcomes measures commonly used in clinical settings: the Strengths and Difficulties Questionnaire (SDQ), the (Child) Outcomes Rating Scale (C/ORS), the Goals Based Outcomes (GBOs), and the Revised Child Anxiety and Depression Scale (RCADS). The RCADS was found to be able to provide the greatest assessment specificity compared to other clinically-oriented measures due to its anxiety subtype subscales (Wolpert et al, 2014).…”
Section: Youth With Histories Of Early-life Adversitymentioning
confidence: 99%
“…The RCADS was found to be able to provide the greatest assessment specificity compared to other clinically-oriented measures due to its anxiety subtype subscales (Wolpert et al, 2014). Another study employed longitudinal confirmatory factor analysis and found support that the RCADS measures anxiety symptoms similarly across time, and thus changes in scores over time likely reflect true changes in anxiety levels (Mathyssek et al, 2013).…”
Section: Youth With Histories Of Early-life Adversitymentioning
confidence: 99%
“…Furthermore, a recent study asserted that the RCADS seems to be one of the most sensitive-to-change tools of the reported outcome measures they reviewed (Wolpert et al, 2015).…”
Section: Introductionmentioning
confidence: 99%